Gaya Kepemimpinan Perguruan Tinggi Kesehatan: Authentic, Tansformational, Authoritarian atau Transactional - Agus Purwanto; Masduki Asbari; Agus Hari Hadi (STIKes Surya Global Yogyakarta, 2020)
Background: The purpose of this study was to analyze the influence of transformational, transactional, authentic and authoritarian leadership styles on the performance of lecturers at a health college in Pati, Central Java. Objective: The purpose of this study was to analyze the influence of transformational, transactional, authentic and authoritarian leadership styles on the performance of lecturers at a health college in Pati, Central Java. Methods: The respondents of this study were 56 lecturers and the method of data collection was by distributing electronic questionnaires to the lecturers of Health College in Pati. Data analysis in this study used SEM (Structural Equation Model) LISREL program version 8.70. Results: The results of the analysis and processing of research data indicated that the leadership of transactional and authoritarian styles of health colleges in Pati showed positive and significant effect on lecturer performance while the transformational and authentic leadership styles do not significantly influence lecturer performance. Conclusion: Transactional and authoritarian leadership style has a positive and significant effect on lecturer performance while the transformational and authentic leadership styles do not significantly influence lecturer performance. Keywords: Authentic; Tansformational; Authoritarian atau Transactional